Biomass of autotrophic dinoflagellates under weak vertical stratification and contrasting chlorophyll levels in subantarctic shelf waters - Gímez, M.I. (2011)
Both the biomass of autotrophic dinoflagellates and its contribution to total chlorophyll were found to increase significantly with seawater temperature and the level of stratification in southern Patagonian waters during spring and winter. The highest peak of biomass corresponded to a single species, Prorocentrum minimum (Pavillard) Schiller, and was detected in middle shelf waters, coinciding with the primary productivity and CO 2 uptake maxima reported for the area under spring conditions. © The Author 2011. Published by Oxford University Press. All rights reserved.